An Analysis of Students Mastery in Finding Verb through “A Million Dreams” Song - Pedelokta, Rahma; Masrul, Masrul; Ayu, Citra (Universitas Pahlawan Tuanku Tambusai, 2024)
This study was conducted to determine students' mastery in finding verbs, especially regular and irregular verbs through